Revocation of the Voting Rights of Persons with Disabilities who are Mentally Impaired - Umar, Risnawati Moh (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
Disability is developmental or developmental. Disability is characterized by significant limitations in intellectual functioning and adaptability. Children with developmental disabilities are children whose intellectual and cognitive abilities are below average. Such conditions can occur when the baby is in the womb or during childbirth, and can also occur in babies after birth. Many parties have revoked the right to vote for disabled people because the  reason is  that they are not considered "qualified" enough. make decisions, especially for persons with intellectual disabilities commonly known as "mentally retarded. The purpose of this writing is to find out whether persons with intellectual disabilities deserve their right to vote, and what are the requirements for the participation of persons with intellectual disabilities in elections. This research method uses a normative juridical method based on space the scope of the Government's role in protecting the rights of persons with disabilities, especially persons with intellectual disabilities in the holding of elections.